2020
DOI: 10.1177/0960327120950007
|View full text |Cite
|
Sign up to set email alerts
|

Nobiletin ameliorates nonylphenol-induced testicular damage by improving biochemical, steroidogenic, hormonal, spermatogenic, apoptotic and histological profile

Abstract: Nonylphenol (NP) is an environmental contaminant, which adversely affects the male fertility due to endocrine disruption and generation of oxidative stress. The current research was planned to assess the effects of nobiletin (NOB), a polymethoxyflavone, on NP-induced testicular damages. Twenty-four male rats were divided into 4 groups: control (0.1% DMSo), NP group (50 mg/kg), NP+NOB group (50 mg/kg + 25 mg/kg), and NOB group (25 mg/kg). Our results revealed that NP brought down the activities of catalase (CAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 78 publications
1
18
0
Order By: Relevance
“…Many studies have revealed that nobiletin could improve the antioxidant defense and decreases lipid peroxidation [75,76,17]. This antioxidant effect may be gifted by modifying the antioxidants gene manifestation [77], free radical reducing action [17], or by decreasing hyperglycemia [78]. The antioxidant effect of nobiletin is in agreement with the results of Bi et al [75].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Many studies have revealed that nobiletin could improve the antioxidant defense and decreases lipid peroxidation [75,76,17]. This antioxidant effect may be gifted by modifying the antioxidants gene manifestation [77], free radical reducing action [17], or by decreasing hyperglycemia [78]. The antioxidant effect of nobiletin is in agreement with the results of Bi et al [75].…”
Section: Discussionsupporting
confidence: 74%
“…Administration of either low or high dose of nobiletin reduced lipid peroxidation and returned changed levels of the antioxidant defenses. Many studies have revealed that nobiletin could improve the antioxidant defense and decreases lipid peroxidation [75,76,17]. This antioxidant effect may be gifted by modifying the antioxidants gene manifestation [77], free radical reducing action [17], or by decreasing hyperglycemia [78].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…β-actin was used as internal control and relative expressions were assessed by 2 -ΔΔCT . Primer sequences of β-actin and target genes are shown in Table 1 as reported previously in Ijaz et al 17 …”
Section: Methodsmentioning
confidence: 99%
“…immunomodulatory [14], nephroprotective [15], neuroprotective and antioxidant properties [16]. It has been reported that nobiletin markedly reduces testicular tissue lipid peroxidation and enhances biochemical and sperm parameters, in addition to enhancement in the epididymal functions [17]. Nobiletin was also known to ameliorate the development of type 2 diabetes mellitus by protecting β-cells from apoptosis [18].…”
Section: Introductionmentioning
confidence: 99%